The mediating role of psychological well-being: Job stress on turnover intention - Wirtadipura, Dian; Alfarizi, Abdul Wahid; Wijaya, Priatna (Institute of Computer Science (IOCS), 2025)
This study aims to examine the effect of job stress on turnover intention with psychological well-being as a mediating variable. A quantitative approach is used with PLS-SEM analysis techniques. Data was obtained through a questionnaire that included three main constructs, namely job stress, psychological well-being, and turnover intention with a total sample of 65 employees. The results prove that job stress has a positive and significant effect on turnover intention, as well as a significant negative effect on psychological well-being. Psychological well-being was also found to have a significant negative effect on turnover intention. In addition, the results showed that psychological well-being significantly mediated the influence of job stress on the intention to leave work. These findings confirm the importance of organizational interventions in managing job stress and improving psychological well-being to reduce the risk of turnover intention